Peningkatan Kemampuan Berbicara Bahasa Inggris Siswa SMAN 1 Kerambitan Melalui Pelatihan English for Restaurant Berbasis Pragmatik Interkultural - Ni Wayan Swarniti; Ni Made Dwi Utari Pusparini; Sandralian Mete; Ni Kadek Ita Sari; Ripal Pangadang Laku Hina (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
The "English for Restaurant" training based on intercultural pragmatics is a community service program aimed at improving the English speaking skills of students at SMAN 1 Kerambitan in the context of restaurant service. This activity emphasizes mastery of speech acts and politeness strategies appropriate to the cultural context of customers. The training was implemented using learning methods such as material presentation, discussions, role play, and interactive restaurant service simulations. Evaluation results showed an improvement in students' abilities with an average post-test score of 84.7, an increase of 22.9 points from the pre-test. Besides linguistic aspects, the training also enhanced students' pragmatic and cultural awareness as well as their confidence in communicating with foreign tourists. This activity provides a positive contribution to the development of English learning based on tourism contexts and intercultural communication.